Effects of antioxidants ascorbic acid and dithiothreitol, or an inhibitor of caspase-3 during cryopreservation of in vitro produced bovine embryos - Carrascal Triana, Erly Luisana (2016)
Experiments described in this study were performed with the overall objective to evaluate whether the addition of antioxidants ascorbic acid (AA) and dithiothreitol (DTT), or inhibitor of caspase-3 (z-DEVD-fmk) during cryopreservation could improve the cryotolerance of in vitro produced bovine embryos. Five experiments were performed and represented as follows: experiment 1, 2 and 3 in Chapter 2 and experiment 4 and 5 in Chapter 3. For all experiments, cumulus oocyte complexes were obtained from ovaries of slaughterhouse cows. Oocytes were in vitro matured, fertilized and cultured to day 7. Blastocysts and expanded blastocysts were randomly assigned to be subjected to controlled-rate freezing following equilibration for 10 min in freezing medium (Hepes-TALP plus 1.5 M ethylene glycol and 0.1 M Sucrose) with treatments as described below. For experiment 1, the embryos were equilibrated in freezing medium containing 0.0; 0.1; 0.3 or 0.5 mM of AA. The embryos into straws were then placed into programmable freezing machine at -6.0 °C to -32 °C prior to being plunged into liquid nitrogen (-196 °C). Then, embryos were thawed and cultured for 72 h in SOF-BE1 supplemented with 10% (v/v) fetal bovine serum at 38.5 oC in a humidified atmosphere of 5% CO2, 5% O2 and 90% N2. Embryos treated with 0.1 mM AA showed higher re-expansion at 24, 48 and 72 h and hatching rates at 72 h compared to control embryos (P<0.05), thus concentration was considered as the optimal for the sequential experiments. For experiment 2 and 3, embryos were cryopreserved in freezing medium containing or not 0.1 mM AA, then were thawed and cultured for 24 h. Intracellular reactive oxygen species levels were reduced (P<0.001) by AA treatment (30.3 ± 2.4) compared with control (49.3 ± 1.9). There was no effect of the total cells number of blastocyst (P>0.05). However, 0.1 mM AA reduced (P<0.001) the percentage of apoptotic cells and DNA fragmentation compared with the control group. Experiments 4 and 5 were conducted to assess the effects of DTT or z-DEVD-fmk during cryopreservation. Blastocyst and expanded blastocysts embryos were equilibrated in freezing medium containing DTT (0, 50, 100 and 200 μM) or z-DEVD-fmk (0, 50, 100 and 200 μM). The embryos into straws were then placed into programmable freezing machine at - 6.0 °C to -32 °C prior to being plunged into liquid nitrogen (-196 °C). Embryos were thawed and then cultured for 72 h. Re-expansion and hatching rates were recorded at 24, 48 and 72 h. There was no effect (P>0.05) of treatment with DTT or z-DEVD- fmk on re-expansion or hatching rates at 24, 48 or 72 h post-thaw. This is the first report that used AA and DTT antioxidants or z-DEVD-fmk a specific inhibitor of the apoptosis in the cryopreservation medium of in vitro produced bovine embryos. In conclusion, addition of AA (0.1 mM) in slow-freezing medium improves the cryosurvival of in vitro produced bovine embryos, reduces intracellular reactive oxygen species levels and DNA fragmentation. DTT and z-DEVD-fmk treatments had no effect on post-thaw embryo survival.